According to Aggie - Beaumont, Mary Richards, 1974-; Kote, Genevieve (Middleton, WI : American Girl, 2017)
When best friends Aggie and Fiona drift apart in fifth grade, Aggie grows to understand that fading friendships are normal, and she makes a new friend who shares more of her interests.
8+.
Keywords: Graphic novels; Friendship -- Fiction; Graphic novels